2016
DOI: 10.1016/j.aeolia.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile of PM 10 and associated health effects in one of the most polluted cities of the world (Ahvaz, Iran) between 2009 and 2014

Abstract: Ahvaz, Iran ranks as the most polluted city of the world in terms of PM10 concentrations that lead to deleterious effects on its inhabitants. This study examines diurnal, weekly, monthly and annual fluctuations of PM10 between 2009 and 2014 in Ahvaz. Health effects of PM10 levels are also assessed using the World Health Organization AirQ software. Over the study period, the mean PM10 level in Ahvaz was 249.5 µg m−3, with maximum and minimum values in July (420.5 µg m−3) and January (154.6 µg m−3), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…In this case, lag structures should be applied. However, we can't use mul tiple lags in one model, as the collinearity between these parameters is high [27]. In order to deal with this problem, distributed lag models (DLM) with smoothing functions have been used [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, lag structures should be applied. However, we can't use mul tiple lags in one model, as the collinearity between these parameters is high [27]. In order to deal with this problem, distributed lag models (DLM) with smoothing functions have been used [28].…”
Section: Discussionmentioning
confidence: 99%
“…In order to deal with this problem, distributed lag models (DLM) with smoothing functions have been used [28]. In studies DLMs have been used for quantifying the cumulative effect of pollutants over multi ple-lagged days [27,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many studies reported increased hospital admittance for respiratory and cardiovascular diseases owing to exposure to dust storms [3,4] . In addition to the public health effects, the agriculture, air traffic, and tourism are also affected [5][6][7] . Dust storms have great environmental effects, including reduction of visibility, soil erosion, ground water salinization, and climatic change.…”
Section: Introductionmentioning
confidence: 99%
“…Dust storms are one of the major natural sources of respirable particulates in Kuwait State [10,11] . Several European [3,12] , USA [13] , Middle East [7,14] , Kuwait [15,16] , and Chinese studies [17] revealed high risk of lung cancer, heart diseases, and chronic obstructive lung diseases among those exposed to PM10.…”
Section: Introductionmentioning
confidence: 99%